Career after graduation: future graduates’ perceptions of job attributes in Small and Medium Enterprises (SMEs) and multi- national corporations (MNCs) - Noor Syakirah Zakaria,; Kee Y Sabariah Kee Mohd Yussof,; Dzurizah Ibrahim,; Rose Patsy Tibok, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Small and Medium Enterprises (SMEs) have made significant contribution towards economic growth especially in the creation of job opportunities in Malaysia. Despite this significant contribution, SMEs are however confronted with numerous issues and challenges regarding quality human capital that is knowledgeable, skillful and with specific expertise in running operations within SMEs. Past studies have shown that graduates preferred employment in large companies including multi-nationals (MNCs) over SMEs despite there being more opportunities due to the rapid growth of the latter in the country. A deciding factor identified in these studies as having influence on graduates’ career choices concerns job attributes. This study is therefore conducted to examine job attributes that form the basis for decisions by graduating final-year students on whether to work with SMEs or MNCs. Twelve (12) job attributes (salary, benefits, management and relationship quality, training and development, career development, level of responsibility given, job marketability, job security, working hours, occupational safety and health, involvement in the job, and a work and family balance policy) are evaluated in this study. The results indicate a large majority of graduating students choose employment in large companies compared to SMEs due to the perception that bigger companies offer better levels of compliance to these job attributes. It is hoped that this evaluation of job attributes will not only help SMEs understand and recognise the needs and desires of potential employees but also spur them towards offering better and more attractive job packages to entice graduates into their organisations.